2017
DOI: 10.3892/mmr.2017.6364
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 induces lung fibroblast to myofibroblast differentiation through NF-κB-mediated TGF-β1 release

Abstract: The proinflammatory factor high-mobility group box protein 1 (HMGB1) has been implicated in the pathogenesis of lung fibrosis; however, the role of HMGB1 in lung fibrosis remains unclear. It has previously been reported that nuclear factor (NF)-κB and transforming growth factor (TGF)-β1 may be involved in lung fibrosis. Therefore, the present study aimed to examine the potential molecular mechanisms that underlie HMGB1-induced lung fibrosis via the regulation of NF-κB and TGF-β1. The results demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…In addition, several studies have reported that NF-κB can directly regulate the expression and secretion of TGF-β1. For example, NF-κB can promote the release of TGF-β1 in pulmonary fibrosis [45], whereas inhibition of the TLR4/MyD88/NF-κB pathway can downregulate the expression of TGF-β1 in glomerular mesangial cells [46]. A similar phenomenon was also observed in myocardia, where the activation of NF-κB can lead to an increase in the expression of its downstream target gene TGF-β1 [47].…”
Section: Discussionmentioning
confidence: 78%
“…In addition, several studies have reported that NF-κB can directly regulate the expression and secretion of TGF-β1. For example, NF-κB can promote the release of TGF-β1 in pulmonary fibrosis [45], whereas inhibition of the TLR4/MyD88/NF-κB pathway can downregulate the expression of TGF-β1 in glomerular mesangial cells [46]. A similar phenomenon was also observed in myocardia, where the activation of NF-κB can lead to an increase in the expression of its downstream target gene TGF-β1 [47].…”
Section: Discussionmentioning
confidence: 78%
“…The important role of HMGB1 in fibroblast activation has been explored in vitro. Studies have shown that HMGB1 can induce fibroblasts to differentiate into myofibroblasts (Wang et al, 2017), an essential process that is responsible for excessive extracellular matrix deposition and tissue contraction during hypertrophic scar formation. Therefore, these data prompted us to investigate the role of HMGB1 in scar development, which is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 exerts its effect in different diseases through the RAGE/NF‐κB signaling pathway; in addition, HMGB1 stimulation increased the activation of NF‐κB and the release of TGF‐β1, as well as α‐SMA and collagen I expression in human lung fibroblasts in vitro . To investigate the mechanism by which miR‐627/HMGB1 modulates TGF‐β1‐induced PF in vitro, we further explored whether miR‐627/HMGB1 could affect TGF‐β1 release through RAGE/NF‐κB signaling in NHLFs.…”
Section: Discussionmentioning
confidence: 99%